Synthesis and ammonolysis of nickel and cobalt tungstates and their characterisation - J.L. Rico; M. Albiter; J. Espino; J.S.J. Hargreaves; M. Ostroumov; L.I. Salcedo; K. Wilson (Journal of Saudi Chemical Society, 2016)
The synthesis and characterization of NiW and CoW compounds are herein reported. The NiWO4 and CoWO4 samples, successfully synthesised by the hydrothermal method, were treated under NH3 to obtain the metal nitride. The SEM micrographs show that this transformation is a topotactic process. Tungsten trioxide was also treated under NH3 at similar operating conditions, and used as a reference. High nitrogen contents after ammonolysis were calculated, however, the percentages were below the theoretical values assuming the formation of pure NiWN, CoWN and WN. The XRD pattern indicates that WON is likely formed after ammonolysis of tungsten oxide whereas phase segregation was observed on the nickel and cobalt samples. Furthermore, the reactivity of the nitride samples as function of temperature was measured under argon and the results show that most of the nitrogen is removed from the cobalt and nickel samples whereas it was partially released from the tungsten specimen.